Polymorphism at codon 72 of the p53 gene is not associated with endometriosis in a Japanese population. - Omori, S; Yoshida, S; Kennedy, S; Negoro, K; Hamana, S; Barlow, D; Maruo, T (2004)
OBJECTIVE: Endometriosis is inherited as a complex trait, which means that multiple susceptibility genes interact with each other and the environment to produce the phenotype. Previous studies have implicated p53, a tumor suppressor gene, as a factor in the development of the disease. In a Japanese population, we investigated the frequency of the p53 polymorphism in women affected with endometriosis. METHODS: We compared the distribution of the p53 codon 72 polymorphism in endometriosis cases (n = 111) and population controls consisting of female neonates (n = 180) by using polymerase chain reaction restriction fragment-length polymorphism analysis in a Japanese population. RESULTS: The frequencies of the three p53 genotypes, Arginine (Arg)/Arg, Arg/Proline (Pro), and Pro/Pro in controls were 39.4%, 41.7%, and 18.9 %, respectively. The crude genotype frequencies in the endometriosis cases were similar to those of the controls (35.2%, 48.6%, and 16.2%, respectively). Using the Arg/Arg genotype as the reference, the odds ratios of the Arg/Pro and Pro/Pro genotypes were 1.30 (95% confidence interval [CI] 0.72-1.86, P =.33) and 0.96 (95% CI 0.47-1.94, P =.91), respectively. Thus, there were no significant differences in the frequency of the p53 codon 72 polymorphism between endometriosis cases and controls in this population. The endometriosis cases with severe disease only were also evaluated, but no significant difference was observed in the frequency of the polymorphism between this subgroup and the controls. CONCLUSION: Our findings suggest that the p53 codon 72 polymorphism is unlikely to be associated with endometriosis in Japanese women.